BRAINROT SEBAGAI TANTANGAN MORAL GENERASI MUDA MUSLIM DI ERA DIGITAL - Rio Ade Firmansyah; Muhammad Kurnaini (Jurnal Manajemen Pendidikan, 2026)
The rapid development of social media in the digital era has generated various new phenomena influencing the behavior of young people, one of which is the phenomenon of brainrot. This term refers to the excessive consumption of fast-paced, repetitive, and shallow entertainment content that may affect individuals’ concentration, self-control, and moral awareness. Digital platforms such as TikTok, Instagram, and YouTube continuously provide short and visually stimulating content, encouraging uncontrolled scrolling behavior that may reduce reflective thinking and interest in meaningful activities. This study aims to analyze the phenomenon of brainrot as a moral challenge for Muslim youth in the digital era. The major focus of this research is the phenomenon of brainrot in social media usage, while the minor focus examines its impact on the moral and ethical behavior of Muslim adolescents. This research employs a descriptive qualitative approach using a library research method by examining various scholarly sources, including academic journals, books, and Islamic literature, particularly the sayings of the Prophet ﷺ as a normative foundation. The findings indicate that the brainrot phenomenon has the potential to weaken moral awareness, shift time priorities, and encourage unproductive digital consumption habits. From an Islamic perspective, such conditions contradict teachings that emphasize responsibility, self-discipline, and the wise use of time.